1982
DOI: 10.1093/ajcn/35.4.678
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced thermogenesis and diminished deposition of fat in response to overfeeding with diet containing medium chain triglyceride

Abstract: The mechanism whereby overfeeding with diet containing medium chain triglyceride (MCT) results in diminished body weight and fat was studied. Fifteen male Sprague-Dawley rats were fitted under anesthesia with gastrostomy tubes and divided into two groups. One group was fed MCT diet, the other an isocaloric diet containing long chain triglyceride (LCT) in excess (150%) of spontaneous calorie intake. Both diets, fed for 6 wk, derived 50% of calories from fat. Basal and norepinephrine (25 micrograms/100 g) stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
86
2
3

Year Published

1989
1989
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(93 citation statements)
references
References 24 publications
2
86
2
3
Order By: Relevance
“…They are also referred to as a readily available source of energy, implying a rapid and almost complete oxidation of MCT (15,20,21). Even the existence of an obligatory oxidation of MCFA with increased heat production has been suggested (22,23). In this study, we found that in both AGA and SGA infants an average of no more than 47% of the administered octanoate was oxidized, with a range of 32 to 64%.…”
Section: Resultsmentioning
confidence: 52%
See 1 more Smart Citation
“…They are also referred to as a readily available source of energy, implying a rapid and almost complete oxidation of MCT (15,20,21). Even the existence of an obligatory oxidation of MCFA with increased heat production has been suggested (22,23). In this study, we found that in both AGA and SGA infants an average of no more than 47% of the administered octanoate was oxidized, with a range of 32 to 64%.…”
Section: Resultsmentioning
confidence: 52%
“…The oxidation rates we found might indicate that in these patients lipogenesis is an important pathway for MCT, whereas fitting less well with the assumption of an obligatory oxidation as a cause of the enhanced thermogenesis that is sometimes encountered on a MCT diet (22,23). If we assume a mean absorption of 85% of the LCT in these patients ( I 6, 17), MCT would account for around 45 % of the absorbed fatty acids.…”
Section: Resultsmentioning
confidence: 55%
“…28 Experiments in laboratory animals have shown that diets high in MCT increase thermogenesis and lead to less fat deposition compared with diets high in LCT. 8,13,14 This has also been demonstrated in a number of acute metabolic rate studies in humans. 15 Scalfi et al have reported similar findings with a mixed meal high in MCT.…”
Section: Discussionmentioning
confidence: 57%
“…7 Other recent studies have shown that thermogenesis is greater in medium chain triglycerides (MCT) diets compared to long-chain triglyceride (LCT) diets, suggesting a reduced efficiency of utilisation. 8 MCT, once hydrolysed, are metabolised more rapidly and completely than LCT. This rapid oxidation leads to greater ketone formation.…”
Section: Introductionmentioning
confidence: 99%
“…10%-35%) either does not affect, or negatively affects the growth performance of young pigs (Allee et al, 1972;Newport et al, 1979) and rats (Lavau and Hashim, 1978;Travis et al, 1979;Baba et al, 1982). Recently, however, researchers have found that a low dietary level of MCT (i.e.…”
Section: Introductionmentioning
confidence: 99%